Numerical analyses of aerodynamic characteristics of integrated L-shaped high-rise building. (December 2017) - Yuan, Weibin; Wang, Zhao; Chen, Hao; Fan, Kexing
Highlights: High-precise 2D and 3D numerical simulations are presented. The details of shape coefficient for different length-to-width ratio are available. The velocity distribution and vortex structure along the central shaft of building are illustrated. The reduced initial resonance region restricts the development of the height of the high-rise buildings. Abstract: Analysis of wind environment around integrated L-shaped buildings of different length-to-width ratios is carried out by using 2D and 3D numerical simulation methods. The Reynolds Stress Model is employed to examine the velocity distributions, surface pressures and vortex structures around the buildings for various different wind directions, in which the initial altitude of resonance region and shape coefficient are discussed in detail. The results show that the velocity along the central shaft is heavily affected by wind direction and the initial altitude of resonance region increases with increased length-to-width ratio. The vortex structure such as generating, evolution and shedding around the L-shape high-rise building under a 45° wind direction is also investigated. The shape coefficients predicted from the simulations are found to be consistent with those recommended in some national codes, although they are not fully considered in the current design codes.